The Influence Of Marketing Public Relations, Brand Image, And After-Sales Service On The Intention To Reuse Indihome Products In Medan City - Siregar, Onan Marakali (SEAN Institute, 2024)
This study examines the influence of Marketing Public Relations, Brand Image, and After-Sales Service on consumer interest in reusing IndiHome products in Medan City. The study employs a quantitative approach with an associative method and involves 96 respondents selected through purposive sampling technique. Multiple linear regression analysis indicates that the three independent variables significantly influence the interest in product reuse. The research findings show that an increase of one unit in marketing public relations by 0.232, brand image by 0.280, and after-sales service by 0.301 respectively increases the interest in reuse. The Adjusted R Square value of 0.644 indicates that 64.4% of the variation in reuse interest can be explained by these three variables. These findings highlight the importance of effective marketing public relations, a strong brand image, and quality after-sales service in enhancing customer retention for IndiHome products. PT. Telkom Indonesia is advised to continuously improve and integrate these strategies to maintain and increase customer loyalty in a competitive market.